Spermatozoa Expression of piR-31704, piR-39888, and piR-40349 and Their Correlation to Sperm Concentration and Fertilization Rate After ICSI. (May 2018) - Cui, Long; Fang, Li; Shi, Biwei; Qiu, Sunquan; Ye, Yinghui
Objective: To investigate the relationship between spermatozoa PIWI-interacting RNAs (piRNAs) levels and semen parameters and to evaluate the role of expression of piRNAs on fertilization and embryo development after intracytoplasmic sperm injection (ICSI) treatment. Methods: One hundred and eighty-six patients with idiopathic male infertility who had undergone first ICSI cycles were enrolled in our study. The levels of piRNAs in spermatozoa were measured by real-time polymerase chain reaction. Semen parameters, including sperm concentration, motility, and morphology, were evaluated. The rates of fertilization, early cleavage, and day 3 good-quality embryo were calculated to assess embryo development potential. Result: Spermatozoa levels of piR-31704 and piR-39888 were decreased in male factor infertility group as compared with control group (for piR-31704, P = .027 and for piR-39888, P = .041, respectively). And these 2 piRNAs were expressed at higher levels in patients with normal sperm concentration compared with subnormal sperm concentration group (for piR-31704, P = .042; for piR-39888, P = .047, respectively), while there were no correlation between the 3 piRNAs expression levels in spermatozoa and the rates of sperm progressive motility and normal sperm morphology. There were significant increases in the levels of all 3 piRNAs in spermatozoa from the group with higher 2PN rates (for piR-31704, P = .002; for piR-39888, P < .001; for piR-40349, P < .001; respectively), but there was no correlation between spermatozoa levels of these 3 piRNAs and the rates of embryo early cleavage, day 3 good-quality embryos and pregnancy. Conclusion: Spermatozoa piRNA levels correlate with sperm concentration and fertilization rate after ICSI. Paternal piRNAs may play a role in fertilization process.